The ideology of racism: essence, formation and transformation in modern conditions - Kurbacheva, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article analyses the essence of the phenomenon of racism. The author carries out a historical and philosophical reconstruction of the formation of the ideology of racism, and also identifies the difficulties of racial research at the present stage of development. The article identifies the distinctive features of the phenomenon of racism from such concepts as chauvinism and xenophobia. The author prescribes the role of social Darwinism and eugenics in the formation of the ideology of racism and captures the key aspects of racism. The author distinguishes two types of racism: classical and modern racism (neo-racism). Classic racism refers to the ideology of domination and subordination, according to which social inequality is explained by anthropomorphic features. Modern racism is a sublimated racism in which biological emphasis is shifted to the sphere of culture and language. The article identifies various forms of racism (everyday, intellectual, institutional) and other forms in which the intersection of classical and sublimated racism is revealed.
Keywords: migration; discrimination; ideology; race; racism; class racism; cultural racism; chauvinism; xenophobia